LAYANAN DIKLAT DI ERA MILLENIAL - Ati Dahniar (Tatar Pasundan: Jurnal Diklat Keagamaan, 2019)
The purpose of this article is to find conceptual answers about the future of millennium training services, including the impact when service is taken over by mechanical systems. It is departs from the fact that at this time the world changes faster since the internet was discovered. Its existence has greatly changed the culture of humanity including the needs of learning. The study results concluded that learning as a basic human need and also adults as leaners will find new momentum through the internet. Training institutions will be forced to adapt in providing their services. Class learning semakain efesien with the presence of virtual class on the internet. On the other hand, the use of the internet in the world of sincerity will also drive to the efficiency of manpower. As the impact of overtaking of conventional service personnel by machines. Keywords: Andragogy; Internet; Services; education; training